2004
DOI: 10.1002/hep.20487
|View full text |Cite
|
Sign up to set email alerts
|

Viral Kinetics During Antiviral Therapy in Patients With Chronic Hepatitis C and Persistently Normal Alt Levels

Abstract: The aim of the present study was to compare viral kinetics between patients with chronic hepatitis C and persistently normal alanine aminotransferase (ALT) levels and those with elevated ALT levels. Kinetic parameters were derived from nonlinear, least square fitting of serum hepatitis C virus RNA quantifications collected from patients with chronic hepatitis C and persistently normal (n ‫؍‬ 20) and elevated (n ‫؍‬ 19) ALT levels before and during treatment with 180 g pegylated interferon ␣-2a once weekly plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
(57 reference statements)
3
17
0
Order By: Relevance
“…This indicates a non-significant association between ALT levels and SVR in univariate and multivariate analyses without GGT levels, but a significant association between ALT and SVR in multivariate analysis including GGT levels. These data are in accordance with findings of reduced efficacy of blocking virus production and lower infected cell loss in patients with elevated GGT levels showing only slight differences in viral kinetics depending on ALT values [22].…”
Section: Discussionsupporting
confidence: 93%
“…This indicates a non-significant association between ALT levels and SVR in univariate and multivariate analyses without GGT levels, but a significant association between ALT and SVR in multivariate analysis including GGT levels. These data are in accordance with findings of reduced efficacy of blocking virus production and lower infected cell loss in patients with elevated GGT levels showing only slight differences in viral kinetics depending on ALT values [22].…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, the GGT quotient tended to be higher in the non-responder group in agreement with other studies [12], [23]; higher GGT levels have been related to advanced fibrosis, steatosis and insuline resistance, which are more common among non-responders [24]. The body weight tended to be higher in non-responder patients; in fact, it has been suggested that obese subjects have an increased expression of the IFN-α signalling inhibitor factor SOCS-3 [25].…”
Section: Discussionsupporting
confidence: 89%
“…This correlation was explained by IFN use, that acts by establish a non-virus-specific antiviral state[15], ultimately leading to a progressive clearance of serum HCV-RNA mediated by both clearance of circulating virions (first-phase) and, afterwards, by the death or clearance of productively-infected hepatocytes (second-phase)[1], eventually leading to serum ALT increase. Indeed, previous kinetics studies in IFN-treated patients showed a positive correlation between lower infected-cell death (δ) and persistently normal ALT values [16]. …”
Section: Discussionmentioning
confidence: 99%